Alleviation of cisplatin-induced neuropathic pain, neuronal apoptosis, and systemic inflammation in mice by rapamycin - Alotaibi, Moureq; Al-Aqil, Faten; Alqahtani, Faleh; Alanazi, Miteb; Nadeem, Ahmed; Ahmad, Sheikh F.; Lapresa, Rebeca; Alharbi, Metab; Alshammari, Abdulrahman; Alotaibi, Muteb; Saleh, Tareq; Alrowis, Raed (Frontiers in Aging Neuroscience, 2022)
Platinum-based chemotherapeutic treatment of cancer patients is associated with debilitating adverse effects. Several adverse effects have been well investigated, and can be managed satisfactorily, but chemotherapy-induced peripheral neuropathy (CIPN) remains poorly treated. Our primary aim in this study was to investigate the neuroprotective effect of the immunomodulatory drug rapamycin in the mitigation of cisplatin-induced neurotoxicity. Pain assays were performed in vivo to determine whether rapamycin would prevent or significantly decrease cisplatin-induced neurotoxicity in adult male Balb/c mice. Neuropathic pain induced by both chronic and acute exposure to cisplatin was measured by hot plate assay, cold plate assay, tail-flick test, and plantar test. Rapamycin co-treatment resulted in significant reduction in cisplatin-induced nociceptive-like symptoms. To understand the underlying mechanisms behind rapamycin-mediated neuroprotection, we investigated its effect on certain inflammatory mediators implicated in the propagation of chemotherapy-induced neurotoxicity. Interestingly, cisplatin was found to significantly increase peripheral IL-17A expression and CD8- T cells, which were remarkably reversed by the pre-treatment of mice with rapamycin. In addition, rapamycin reduced the cisplatin-induced neuronal apoptosis marked by decreased neuronal caspase-3 activity. The rapamycin neuroprotective effect was also associated with reversal of the changes in protein expression of p21Cip1, p53, and PUMA. Collectively, rapamycin alleviated some features of cisplatin-induced neurotoxicity in mice and can be further investigated for the treatment of cisplatin-induced peripheral neuropathy.